2013
DOI: 10.11622/smedj.2013067
|View full text |Cite
|
Sign up to set email alerts
|

Successful extracorporeal liver dialysis for the treatment of trimethoprim-sulfamethoxazole-induced fulminant hepatic failure

Abstract: (1) TMP-SMZ-induced drug rash with eosinophilia and systemic symptoms (DRESS) syndrome is a rare but recognised complication, occurring in 0.01%-0.1% of patients, (2) and can cause fulminant hepatic failure. We describe a case of TMP-SMZinduced DRESS syndrome associated with fulminant hepatic failure in an adolescent who was successfully managed with extracorporeal liver dialysis. CASE REPORTA 17-year-old Chinese male adolescent presented to our emergency department with fever, myalgia and a nonpruritic maculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…As mentioned above, TMP/SMX-induced fulminant hepatitis is a component of DRESS syndrome, occurring as soon as 1 day, or up to 6 weeks after first exposure and it managed usually successfully with corticosteroid and antihistamine use [ 72 ]. However, based on our review, the shortest latency period for TMP/SMX was 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, TMP/SMX-induced fulminant hepatitis is a component of DRESS syndrome, occurring as soon as 1 day, or up to 6 weeks after first exposure and it managed usually successfully with corticosteroid and antihistamine use [ 72 ]. However, based on our review, the shortest latency period for TMP/SMX was 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Roales-Gómez et al 38 described MARS use, although patient did not responde well, and patients was eventually submmited to OLT. Ng et al 23 reported a pediatric patient that underwent MARS in the intensive care unit, with satisfactory response.…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports recorded in the literature showed DRESS syndrome and significant hepatic injury (Table 1). In these studies, most of the patients were treated with corticosteroids 9‐30 . Among patients needing liver transplantation, there was approximately 50% perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Roales‐Gómez et al 39 described MARS use, although the patient did not respond well, and patients eventually underwent OLT. Ng et al 24 reported a pediatric patient that underwent MARS in the intensive care unit with a satisfactory response.…”
Section: Discussionmentioning
confidence: 99%